Sinus rhythm maintenance following DC cardioversion of atrial fibrillation is not improved by temporary precardioversion treatment with oral verapamil. (14th April 2004) - Lindholm, C-J A; Fredholm, O; Möller, S-J; Edvardsson, N; Kronvall, T; Pettersson, T; Firsovaite, V; Roijer, A; Meurling, C J; Platonov, P G; Olsson, S B
Abstract : Objective: To evaluate prospectively the effects of pretreatment with verapamil on the maintenance of sinus rhythm after direct current (DC) cardioversion. Design: Randomised, active control, open label, parallel group comparison of verapamil versus digoxin. Settings: Multicentre study in three teaching and three non-teaching hospitals in Sweden. Patients: 100 consecutive patients with atrial fibrillation (AF) of at least four weeks' duration and indications for cardioversion were assigned randomly to two groups, one treated with verapamil (verapamil group) and the other with digoxin (digoxin group) before cardioversion. Fifty patients were assigned randomly to each treatment arm. After dropout of four patients from the digoxin group and seven patients from the verapamil group, data obtained from 89 patients were analysed. Interventions: After randomly assigned pretreatment with either verapamil or digoxin for four weeks, DC cardioversion was performed. If sinus rhythm was restored then verapamil treatment was discontinued. Main outcome measures: The rate of AF recurrence was assessed one, four, eight, and 12 weeks after cardioversion. Results: 6 patients in the verapamil treated group and none in the digoxin treated group reverted to sinus rhythm spontaneously (p < 0.05). DC cardioversion restored sinus rhythm in 24 of 37 (65%) patients in the verapamil group and 41 of 46 patients (89%) in the digoxin group (p < 0.05). After 12 weeks' follow up 28% (13 of 46) of digoxin pretreated patients versus 9% (four of 43) of verapamil pretreated patients remained in sinus rhythm (p < 0.05). Conclusion: Pretreatment with verapamil alone does not improve maintenance of sinus rhythm after DC cardioversion in patients with AF. The rate of spontaneous cardioversion may be improved by verapamil.